TRAINING INITIATIVES FOR WEAVERS’ SKILL ENHANCEMENT: AN IMPACT ASSESSMENT STUDY (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The study’s goal is to examine how a training  program affects the development of a weaver’s  skills. Handloom training programs are necessary  for the advancement and upgradation of  weaving techniques (Balakrishnan & Nadu,  2019). Handloom is the traditional cottage  industry of Orissa and is performed by weavers  for generations to earn a livelihood with self employment. Skill has a multilevel role to play in  the handloom industry, whether it’s learning to  weave or utilising technology to boost weaving  output. Due to the present advancement  in technology, this industry is facing stiff  completion in the market for substances.  To overcome the situation, market-oriented  products with colour fastness are required which  can be done with skills training for the weavers.  For this, data have been collected from 110  trained weavers who have undergone handloom  training in Bargarh District. Paired Sample  t-test was used to analyse the collected data, and  Cohen’s D Test was used to calculate the effect  size. The study discovered that after completing  the training programme, the weavers’ skills  significantly improved.
Keywords: Training; Weaving; Skill; Skill Handloom